P9 Evaluating the perspectives of trainees on the hepatology training pathway. (28th September 2020) - Bhuva, Meha; Tavabie, Oliver; Nayagam, Jeremy; Rahim, Mussarat; FitzPatrick, Michael; Griffiths, William; Snowdon, Victoria Katherine
Abstract : Background: Obtaining a CCT (Certificate of Completion of Training) in Hepatology requires 24 months of dedicated Hepatology training. The non-academic pathway includes an advanced training program (ATP) year which is nationally competitive (17 posts) and often geographically challenging. Shape of Training will enforce a reduction in Gastroenterology training to 4 years requiring trainees to make earlier and more restrictive career decisions (e.g. dropping colonoscopy), and demands training program designers to provide sufficient timely training opportunities while meeting workforce requirements. Of note, the number of Hepatologists nationally is insufficient. With respect to Hepatology training, we sought to gauge the opinions of ST3/4 Gastroenterology trainees to help inform program design. Methodology: Quantitative and qualitative data was collected using anonymised questionnaires which were completed by trainees attending the BSG-led 'Introduction to Gastroenterology Day 2019' with subsequent framework analysis of qualitative data. Results: 44 trainees completed the questionnaire and 32 (73%) are considering a career in Hepatology (5 'definitely', 17 'probably', 10 'maybe'). Reasons include: positive clinical experiences, Hepatology patients and disease pathogenesis, and personal circumstances (mainly geographical). 5/32 (16%) aim to work in a Level 3 centre, 15/32 (47%) in a level 2 centre, 3/32 (9%) in a district general hospital (DGH) with the remainder undecided. Of note (considering the whole dataset), 5/44 (11%) are unsure if there is a transplant centre in their deanery. 10/32 (31%) would be able to move and 7/32 (22%) would want to move for an ATP. 16/32 (50%) trainees considering Hepatology favour current national allocation, regarding it as a fair process. The remaining 16/32 (50%) favour local allocation largely due to availability of level 2/3 centres in their deanery. Of the 22 trainees who are 'probably' or 'definitely' considering Hepatology, 12/22 (55%) are willing to drop colonoscopy training (including 4/5 (80%) who are 'definitely' considering Hepatology). Discussion: Our results suggest that a significant proportion of early trainees are interested in a career in Hepatology providing reassurance regarding any potential increase in ATPs. Furthermore, outcomes regarding dropping colonoscopy (as necessitated by a shorter training program) are reassuring. Trainees are less interested in DGH Hepatology which is concerning as this is where the need is (Lancet Commission 2019). National ATP allocation is generally supported but would benefit from greater post coverage geographically. Providing trainees with salient information early- ideally prior to commencing specialty training- will facilitate decision making (including choosing or moving deaneries) to permit successful career planning.